Sensory studies in adult-onset primary torsion dystonia - O'Dwyer, John Philip (Trinity College. Institute of Neuroscience, 2011)
Dystonia is a disorder of movement characterized by prolonged muscle contractions, causing sustained twisting movements and abnormal postures of the affected body parts. Sensory symptoms including pain are frequently reported in dystonia, and many patients use sensory tricks to alleviate the muscle contractions. Sensory changes have been found in dystonia including abnormalities of spatial discrimination thresholds, somaesthetic temporal discrimination thresholds, and sensory evoked potentials. In addition, the sensory homuncular arrangement at many levels is disorganized, and the sensory cortex shows overlapping sensory fields and enlargement in unaffected and affected sides in focal dystonia. Are these an epiphenomenon of the motor problem, or if they are primary does it suggest that dystonia is disorder of sensorimotor integration? The clinical phenotype has a low penetrance in adult-onset primary torsion dystonia (AOPTD), but would it be possible to find sensory abnormalities in unaffected family members?
Keywords: Neurology, M.D.; M.D. Trinity College Dublin